Measuring Differences in the Job Satisfaction of School Teachers Working in Government and Private Sector Schools in the Rural Area of Rajasthan - Bhatt, Anil K.; Menaria, Rajendra (International Journal For Research In Business, Management And Accounting, 2017)
Satisfaction refers to the level of fulfillment of one’s needs, wants and desire. Satisfaction depends basically upon what an individual wants from the world, and what he gets. It is a measure of how happy workers are with their job and working environment. The purpose of this quantitative study was to investigate the differences in the perception of School teachers working in the government and private sector schools for their job satisfaction. The sample of 300 primary school teachers were taken out of which 133 were working in private and 167 were working in government sector in the rural area of Rajasthan. The results show there is a significant difference for both hygiene and motivational factor for job satisfaction from their current job. Using the independent sample t test with 300 School teachers differences were identified with a sample from various schools.